2013
DOI: 10.1108/jepp-08-2011-0010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-sharing through social interaction in a policy-driven industrial cluster

Abstract: Purpose -The purpose of this paper is to investigate whether knowledge-flows through social interaction occur within the context of a policy-driven industrial cluster. Design/methodology/approach -The paper follows a single-case approach, adopting Malaysia's Multimedia Super Corridor cluster as the unit of analysis. Semi-structured interviews with firm-and non-firm-respondents in the cluster constitute the prime source of data. Findings -Spontaneous social interaction leading to knowledge diffusion within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…The theme of inter-organizational and collaborative networks has been taking up broad space in academic discussions and organizational studies (Oliver, 1990; Grandori and Soda, 1995; Powell et al , 1996; Oliver and Ebers, 1998; Pöyhönen and Smedlund, 2004; López-Sáez et al , 2010; Mariotti, 2011; Gardet and Mothe, 2012; Jardon and Martos, 2012; Richardson, 2013; Suárez, 2013; Khalique et al , 2015; Baker et al , 2016; Zach and Hill, 2017; Belso-Martinez and Diez-Vial, 2018), offering a precious base of shared interests with great potential for dialogue between the various branches of social science (Grandori and Soda, 1995; Balestrin et al , 2008), mainly when formed between SMEs (Pöyhönen and Smedlund, 2004; López-Sáez et al , 2010; Gardet and Mothe, 2012; Jardon and Martos, 2012; Richardson, 2013; Suárez, 2013; Khalique et al , 2015; Baker et al , 2016). Suárez (2013) perceives networks as forms of organization that connect actors at different points, through which spaces of interaction and sharing are formed with their dynamics.…”
Section: Intellectual Capital and Organizational Performance In Small And Medium-sized Enterprises Knowledge-based Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The theme of inter-organizational and collaborative networks has been taking up broad space in academic discussions and organizational studies (Oliver, 1990; Grandori and Soda, 1995; Powell et al , 1996; Oliver and Ebers, 1998; Pöyhönen and Smedlund, 2004; López-Sáez et al , 2010; Mariotti, 2011; Gardet and Mothe, 2012; Jardon and Martos, 2012; Richardson, 2013; Suárez, 2013; Khalique et al , 2015; Baker et al , 2016; Zach and Hill, 2017; Belso-Martinez and Diez-Vial, 2018), offering a precious base of shared interests with great potential for dialogue between the various branches of social science (Grandori and Soda, 1995; Balestrin et al , 2008), mainly when formed between SMEs (Pöyhönen and Smedlund, 2004; López-Sáez et al , 2010; Gardet and Mothe, 2012; Jardon and Martos, 2012; Richardson, 2013; Suárez, 2013; Khalique et al , 2015; Baker et al , 2016). Suárez (2013) perceives networks as forms of organization that connect actors at different points, through which spaces of interaction and sharing are formed with their dynamics.…”
Section: Intellectual Capital and Organizational Performance In Small And Medium-sized Enterprises Knowledge-based Networkmentioning
confidence: 99%
“…Within networks, knowledge needs to be understood as embedded in inter- and intra-organizational social relationships (Hughes et al , 2009). However, only social interactions have not been able to lead to the diffusion of knowledge in the networks (Richardson, 2013), because merely creating structural links between organizations does not necessarily produce the creation and sharing of information and knowledge (Hughes et al , 2009; Richardson, 2013). One of the problems that arise in the literature is that these issues have been dealt with separately, making a deeper understanding of the phenomenon difficult.…”
Section: Intellectual Capital and Organizational Performance In Small And Medium-sized Enterprises Knowledge-based Networkmentioning
confidence: 99%
“…In this respect, Ghauri, Lutz, and Tesfom (2003) observed that clusters could be useful in solving export-marketing problems for manufacturing firms in developing countries, where the authors discussed conditions under which learning and capabilities exploitation can occur in Brazilian clusters. However, many of these studies have focused on the supportive role of government and public agencies on clusters performance (e.g., Kamran et al, 2017;Richardson, 2013), indicating that when the social bonding in a given cluster is weak, government interventions are of greater significance. Another stream of literature has investigated other aspects of clustering in developing countries, including trust and inter-firm relationships (e.g., Chen et al, 2017;Sarach, 2015;Vanzettine et al, 2017), value creation and competitive advantage (e.g., Lei & Huang, 2014), knowledge systems and innovation (e.g., Hashino & Otsuka, 2013;Richardson, 2013), and social capital and responsibility (e.g., Kamath, 2013;Lund-Thomsen & Pillay, 2012).…”
Section: Industrial Cluster In Developing Countriesmentioning
confidence: 99%
“…Raising a country's standard of living was dependent on the capacities of firms to achieve high levels of productivities by increasing productivities over time. Manufacturers face intense competition, uncertainty, and continuous change in 21 st century global markets; providing a product with high-quality at a low-cost does not guarantee success (Richardson, 2013). This study broadened the scope of research available to the organizations and political leaders of Brownsville, Texas, and Matamoras, Mexico, who are exploring alternative ways to create new jobs through industrial clusters.…”
Section: Purpose and Significance Of The Studymentioning
confidence: 99%